Percepción de la calidad en los clientes del servicio de Kukayo-Catering - Guanoquiza Castro, María Isabel (2023)
The present investigation was carried out in the Kukayo company - catering is located in Quito, province of Pichincha, Ecuador of the AV. Galo plaza Lasso 82, entitled "Perception of Quality in Kukayo-Catering Service Customers" aims to analyze the quality of the service of the Kukayo catering company and to know the parameters that were used to achieve a better service through the application of the Servqual model that consists of five dimensions (reliability, sensitivity, security, empathy and tangible elements) made up of 22 items that help to measure the expectations and perceptions that customers have.